The Sound of Your Voice, Only Really Far Away - Dowell, Frances O'Roark (New York : Atheneum Books for Young Readers, 2013)
Best friends Marylin and Kate compete for limited school resources when Kate helps her boyfriend seek funding for the Audio Lab, while Marylin covers her interest in the student body president by claiming she only wants his support for new cheerleading uniforms.
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Popularity -- Fiction